Strategi kepala sekolah dalam pengembangan budaya religius di lembaga pendidikan analisis systematic literature review - Ningsi Jaya Sari; Hasbi; Firman (Sekolah Tinggi Ilmu Tarbiyah Madani Yogyakarta, 2023)
The background of this thesis is improving the morals and morals of students at this time, namely by the existence of a religious culture that gives rise to religious values ​​in students. Of course, to carry out this strategy, the leader and strategy maker in the school environment is the principal and who will be the spearhead or main role. The purpose of this research is to map the results of the review that has been carried out regarding the principal's strategy in developing a religious culture in schools and to describe the strategies that have been carried out by the principal in developing a religious culture in schools. Based on the type of data used in this study, the authors used a descriptive research type using the Systematic Literature Review (SLR) method. In this selection criteria, the types of research articles and research articles that can be accessed in full (full text) are written. The literature collection procedure was carried out in detail. The model to be used is the PRISMA (Preferred Reporting Items For Systematic Review and Meta-analysis) model of articles published from 2019-2023 or the last 5 years. The result showed that the 7 types of articles analyzed explained that the success of the principal’s strategy based on the work program and its performance and the management of the principal became a supporter of its success in developing a religious culture in schools and the success of educational programs through the learning the process was strongly influenced by many factors, one of wich was availability of adequate educational facilities and infrastructure along with optimal utilization and management.